The Semiotic of Deconstructivism Between Eisenman and Van Eyck - Sharara, Hussein Abdulhussein (Journal of engineering sciences and information technology, 2022)
The research examines the phenomenon of deconstructivism as a contemporary architectural movement that originated on the ruins of postmodernism, and discusses its developments based on how it was approached by two of its architects, Aldo Van Eck and Peter Eisenman. The research also addresses the problem of interpreting the semantic dimension of deconstructivism and its readings that neglected the semiotic and epistemological dimensions that its architects sought to include in their work as a philosophical foundation, and it is the knowledge gap that the research sought to address which highlighted the importance of researching the subject and the need for such architectural studies of a philosophical nature. The research explores the dimensions of deconstructive architecture with inductive logic that takes an analytical turn to highlight the philosophical dimension, concluding that in-depth reading of the work of deconstructivist architects highlights the need for careful and detailed consideration of the ethnological dimension that seeks to interpret the function and significance of the architects’ work. The research discusses, in an introduction, two sections, and a summary, the deconstructive semiotics between Eisenman and Van Eyck based on the ideas and philosophy of Jacques Derrida; Analyzing the works of Frank Gehry and Zaha Hadid, and comparing their architecture. This paper is concluded, by discussing their works, that deconstructivism as an architectural movement carried semiotic and epistemological connotations with its theoretical base. This research recommends the necessity of studying the philosophical and cognitive dimensions of architecture.